Secagem convectiva de folhas visando a obtenção de compostos bioativos via extração supercrítica - Canabarro, Nicholas Islongo (2019)
In this work, an investigation through experimentation and mathematical modeling was carried out with the intention of evaluating the drying process of pitangueira (Eugenia uniflora L.) and olive tree (Olea europaea L.) leaves in a conveyor belt drier, aiming the extraction of extracts by the supercritical carbon dioxide extraction. A complete characterization of both leaves as to their physical properties, such as characteristic dimensions, specific mass, initial moisture content, equilibrium moisture and surface morphology was performed. The results indicated that the leaves had distinct physical characteristics, with surface areas of 24 ± 1 and 8 ± 1 cm² for pitangueira and olive leaves, respectively. In relation to the morphology, the leaves of pitangueira present striated trichomes while the olive leaves have peltate trichomes. Drying tests were performed at temperatures of 50, 60 and 70 ° C using a forced convection oven and a pilot scale dryer. In the oven drying it was observed that the temperature has a significant influence on the drying of the leaves and that the internal mass transfer mechanisms control the drying process. In addition, the morphological differences of the leaves impose different resistance to the mass transfer during the drying process and the olive leaves have a more pronounced rolling than the pitangueira leaves. In the drying on the conveyor belt, in all the conditions imposed, leaves with discharge humidity were obtained within the range considered ideal for the supercritical extraction process (7 to 18% b.u.). The behavior of the drying kinetics was similar to that of the oven, and the peltate trichomes present in the olive leaves contribute to the increase of resistance to mass transfer in comparison to the leaves of pitangueira. The two-phase model accurately predicted the discharge moisture and temperature of the leaves during drying in the conveyor belt dryer. In the supercritical extraction tests, preliminary studies showed that the condition of 80 ° C and 250 bar is the most adequate condition to obtain the supercritical extracts of the pitanga leaves, presenting higher yields and higher extraction rates. The models of Sovová (1994) and Spline provided good agreements with the experimental data of the overall extraction curves in all conditions investigated. Drying had a significant influence on the extraction yields, as well as on the concentration of phenolic compounds and on the values of antioxidant activity for both leaves. In the case of the pitangueira leaves, the condition determined as the most appropriate was the drying done at 60 ° C and 60 minutes, since higher yields, phenolic compound concentrations and antioxidant activity values were obtained. In addition, in this condition also the lowest energy expenditure for the removal of moisture was reached. In the case of olive leaves, the best drying condition was 50 ° C and 180 minutes for the extraction yield and 60 ° C and 120 minutes for the concentration of phenolic compounds and antioxidant activity, showing that the drying conditions are very important in extraction of bioactive compounds via supercritical dioxide carbon extraction.